Modifying the secondary school environment to reduce bullying and aggression: the INCLUSIVE cluster RCT - Chris Bonell; Elizabeth Allen; Emily Warren; Jennifer McGowan; Leonardo Bevilacqua; Farah Jamal; Zia Sadique; Rosa Legood; Meg Wiggins; Charles Opondo; Anne Mathiot; Joanna Sturgess; et al. (NIHR Journals Library, 2019)
Background: Bullying, aggression and violence among children and young people are some of the most consequential public mental health problems. Objectives: The INCLUSIVE (initiating change locally in bullying and aggression through the school environment) trial evaluated the Learning Together intervention, which involved students in efforts to modify their school environment using restorative approaches and to develop social and emotional skills. We hypothesised that in schools receiving Learning Together there would be lower rates of self-reported bullying and perpetration of aggression and improved student biopsychosocial health at follow-up than in control schools. Design: INCLUSIVE was a cluster randomised trial with integral economic and process evaluations. Setting: Forty secondary schools in south-east England took part. Schools were randomly assigned to implement the Learning Together intervention over 3 years or to continue standard practice (controls). Participants: A total of 6667 (93.6%) students participated at baseline and 5960 (83.3%) students participated at final follow-up. No schools withdrew from the study. Intervention: Schools were provided with (1) a social and emotional curriculum, (2) all-staff training in restorative approaches, (3) an external facilitator to help convene an action group to revise rules and policies and to oversee intervention delivery and (4) information on local needs to inform decisions. Main outcome measures: Self-reported experience of bullying victimisation (Gatehouse Bullying Scale) and perpetration of aggression (Edinburgh Study of Youth Transitions and Crime school misbehaviour subscale) measured at 36 months. Intention-to-treat analysis using longitudinal mixed-effects models. Results: Primary outcomes - Gatehouse Bullying Scale scores were significantly lower among intervention schools than among control schools at 36 months (adjusted mean difference -0.03, 95% confidence interval -0.06 to 0.00). There was no evidence of a difference in Edinburgh Study of Youth Transitions and Crime scores. Secondary outcomes - students in intervention schools had higher quality of life (adjusted mean difference 1.44, 95% confidence interval 0.07 to 2.17) and psychological well-being scores (adjusted mean difference 0.33, 95% confidence interval 0.00 to 0.66), lower psychological total difficulties (Strengths and Difficulties Questionnaire) score (adjusted mean difference -0.54, 95% confidence interval -0.83 to -0.25), and lower odds of having smoked (odds ratio 0.58, 95% confidence interval 0.43 to 0.80), drunk alcohol (odds ratio 0.72, 95% confidence interval 0.56 to 0.92), been offered or tried illicit drugs (odds ratio 0.51, 95% confidence interval 0.36 to 0.73) and been in contact with police in the previous 12 months (odds ratio 0.74, 95% confidence interval 0.56 to 0.97). The total numbers of reported serious adverse events were similar in each arm. There were no changes for staff outcomes. Process evaluation - fidelity was variable, with a reduction in year 3. Over half of the staff were aware that the school was taking steps to reduce bullying and aggression. Economic evaluation - mean (standard deviation) total education sector-related costs were £116 (£47) per pupil in the control arm compared with £163 (£69) in the intervention arm over the first two facilitated years, and £63 (£33) and £74 (£37) per pupil, respectively, in the final, unfacilitated, year. Overall, the intervention was associated with higher costs, but the mean gain in students' health-related quality of life was slightly higher in the intervention arm. The incremental cost per quality-adjusted life year was £13,284 (95% confidence interval -£32,175 to £58,743) and £1875 (95% confidence interval -£12,945 to £16,695) at 2 and 3 years, respectively. Limitations: Our trial was carried out in urban and periurban settings in the counties around London. The large number of secondary outcomes investigated necessitated multiple statistical testing. Fidelity of implementation of Learning Together was variable. Conclusions: Learning Together is effective across a very broad range of key public health targets for adolescents. Future work: Further studies are required to assess refined versions of this intervention in other settings. Trial registration: Current Controlled Trials ISRCTN10751359. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 7, No. 18. See the NIHR Journals Library website for further project information. Additional funding was provided by the Educational Endowment Foundation.